Exploring the Relationship Between Tax Socialization and Tax Compliance in MSMEs: A Case Study from North Kolaka District - Joana, Fery Insan; Arfandi, Muhammad (Phinisi Applied Accounting Journal, 2024)
Abstract. This study examines the impact of tax socialization on tax compliance among MSME actors in North Kolaka District. Using a regression analysis, the research analyzes how socialization efforts influence tax compliance behavior. The results show a significant positive relationship between tax socialization and tax compliance, with 52.7% of the variation in compliance explained by the level of socialization. As socialization efforts increase, tax compliance tends to improve, with a strong correlation (r = 0.726) between the two variables. These findings suggest that enhanced tax socialization can effectively encourage MSMEs to meet their tax obligations. The study highlights the importance of targeted educational programs in improving compliance rates and fostering a culture of tax responsibility among MSMEs in North Kolaka. Keywords: North Kolaka District; Regression Analysis; Tax Compliance; Tax Socialization; SMEs (Small and Medium Enterprises) Abstrak. Penelitian ini mengkaji pengaruh sosialisasi perpajakan terhadap kepatuhan pajak pada pelaku UMKM di Kabupaten Kolaka Utara. Dengan menggunakan analisis regresi, penelitian ini menganalisis bagaimana upaya sosialisasi memengaruhi perilaku kepatuhan pajak. Hasil penelitian menunjukkan adanya hubungan positif yang signifikan antara sosialisasi perpajakan dan kepatuhan pajak, dengan 52,7% variasi kepatuhan dapat dijelaskan oleh tingkat sosialisasi. Seiring dengan meningkatnya upaya sosialisasi, kepatuhan pajak cenderung meningkat, dengan korelasi yang kuat (r = 0,726) antara kedua variabel. Temuan ini menunjukkan bahwa peningkatan sosialisasi perpajakan dapat secara efektif mendorong UMKM untuk memenuhi kewajiban pajaknya. Penelitian ini menyoroti pentingnya program edukasi yang ditargetkan dalam meningkatkan tingkat kepatuhan dan membangun budaya tanggung jawab pajak di kalangan UMKM di Kabupaten Kolaka Utara. Kata kunci: Analisis Regresi; Kabupaten Kolaka Utara; Kepatuhan Pajak; Sosialisasi Perpajakan; UMKM